Pengaruh Derajat Kesesuaian Orientasi Strategi, Lingkungan Eksternal, Struktur Saluran Ekspor, Budaya Organisasi dan Kinerja Ekspor - Muafi, Muafi (Jurnal Manajemen dan Kewirausahaan, 2009)
This research therefore uses configuration and contingency theory to establish if there is a relationship between export performance and the level of ‘fit’ between a firm’s strategic orientation and its context. The approach of configuration and contingency approach are carried in order the firm has fit. The organization will be designed and positioned better, effectively and efficiently in every its activity. The sample of research were taken from the manufacturing firms in East Java. The technique of sampling used non probability sampling. The examining of configuration and contingency approach used regression euclidience distance. The result of configuration and contingency approach explained that there is fit between strategic orientation and the elements of contingency such as external environment, export channel structure and organizational culture. However, if it be analized deeply, there is no fit between the strategic orientation of entrepreneur and contingency variable such as external environment. There is also no fit between strategic orientation of conservatif and export channel structure approach contingency.